2023
DOI: 10.1123/jege.2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Effective Training Practices in League of Legends: A Qualitative Exploration

Abstract: While scientific interest in electronic sports (esports) is steadily growing, there remains an absence of research evidence concerning training practices in specific esports such as League of Legends. Anecdotal evidence suggests that current approaches to training may be suboptimal in terms of performance and, concerningly, linked to negative consequences for player health and well-being. In order to address the lack of literature and aid understanding of the (in)effectiveness of current training practices in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…This highlights the need to find more effective practice solutions and to prevent unhealthy practice behaviors, negative lifestyle outcomes, and burnout associated with esports ( DiFrancisco-Donoghue et al, 2019 ; Salo and Information Resources Management Association (IRMA), 2021 ). Results and suggestions from the studies by Pluss et al also align with the findings of a study conducted by Abbott et al (2022) which investigated the perceived effectiveness of practice in LoL. Results indicated that players evidenced a lack of perceived effectiveness within their current training environment and believed that the predominant grind (i.e., a high quantity of games) approach was not the most effective method for the development and achievement of expertise.…”
Section: Skill Development and Current Esports Researchsupporting
confidence: 61%
See 1 more Smart Citation
“…This highlights the need to find more effective practice solutions and to prevent unhealthy practice behaviors, negative lifestyle outcomes, and burnout associated with esports ( DiFrancisco-Donoghue et al, 2019 ; Salo and Information Resources Management Association (IRMA), 2021 ). Results and suggestions from the studies by Pluss et al also align with the findings of a study conducted by Abbott et al (2022) which investigated the perceived effectiveness of practice in LoL. Results indicated that players evidenced a lack of perceived effectiveness within their current training environment and believed that the predominant grind (i.e., a high quantity of games) approach was not the most effective method for the development and achievement of expertise.…”
Section: Skill Development and Current Esports Researchsupporting
confidence: 61%
“…These include first-person shooters (FPS; e.g., Counter-Strike: Global Offensive (CS:GO), Valorant, Call of Duty) and massive online battle arenas (MOBA: e.g., League of Legends (LoL), Dota2). However, across genres, research has indicated that key stakeholders (i.e., professional players and teams) report dissatisfaction with their training and development processes ( Abbott et al, 2022 ; Sabtan et al, 2022 ). Furthermore, it is common for high turnover within rosters in esports ( LeNorgant, 2019 ) which restricts talent development and can impede on the coaching process.…”
Section: Introductionmentioning
confidence: 99%
“…Self-regulated breaks during long play sessions and tournaments, such as simple walks, small breaks with other activities, or long-term removal from esports, have also been suggested in other contexts and esports modalities [62]. Variations on how to train, more e cient and speci c scenario practices, or training with stronger opponents could improve esports training while reducing excessive esports practice [21]. Simultaneously, those strategies could help prevent mental (e.g., mental fatigue) and physical health (e.g., back pain) problems in esports players.…”
Section: Optimising Esports Training and Schedulingmentioning
confidence: 99%
“…Several participants explained that esports players should improve their lifestyle habits to promote and prevent health problems. Players recognise that physical activity, nutrition, sleep, and tness could bene t esports performance [17,21,60]. For example, based on studies on dietary patterns for cognition and mental health (e.g., mood, cognition) conducted with adolescents, university students and older people [63, 64, 65], healthy diets could give players the extra edge to enhance esports performance and mental health.…”
Section: Improving Lifestyle Habitsmentioning
confidence: 99%
See 1 more Smart Citation